Uji Aktivitas Antibakteri Formula Pasta Gigi Ekstrak Batang Karui (Harrisonia Perforata Merr.) Terhadap Bakteri Streptococcus Mutans - Wardatul Nurjannah; Yusriadi Yusriadi; Arsa Wahyu Nugrahani (Biocelebes, 2018)
Karui (Harrisonia perforata Merr.) is one of the many species that live in tropical regions such as Central Sulawesi (Palu) and has antibacterial activity. This research aims to find the variation effect of karui stem extract (Harrisonia perforata Merr.) in toothpaste towards stability of physical quality and antibacterial activity bacteria Streptococcus mutans. The concentrations of karui stem extract 1%, 2%, and 3% in toothpaste tested for antibacterial activity using pitting method which further tested for statistical analysis "One Way Anova" using SPSS 16.0 software. The results of the evaluation of toothpaste Karui stem extract F1 (1%), F2 (2%), and F3 (3%) showed that the test of the organoleptic and homogenity has no significant difference during the storage time (28 days) but the test at pH, viscosity, and the scatter has significant difference. The Formula of karui stem ekstract with 3 concentrations F1 (1%), F2 (2%), and F3 (3%) forming an average diameter of antibacterial inhibitory 6.65 mm; 7.14 mm; and 9.85 mm. The results of statistical analyzed from toothpaste test diameter inhibitory zone showed an unsignificant difference. Keywords: toothpaste, extract, karui (Harrisonia perforata Merr.), Streptococcus mutans